A non-enzymatic doxycycline absorbance sensor based on manganese-doped zinc sulfide nanoparticles coated with chitosan - Son Hai Nguyen; Mai Thi Tran (PLoS ONE, 2025)
The need for doxycycline detection is urgent because it is a vital antibiotic extensively utilized to combat bacterial diseases in humans and animals, and it is now at the forefront of the global battle against antibiotic resistance. Our research introduces an absorbance biosensor that employs chitosan-capped ZnS nanoparticles doped with manganese without an enzyme to address this critical need. Our study highlights the sensor’s robust performance with nearly 100% recovery and stability over time to detect doxycycline from 0 to 72.2 pM. Limits of detection and quantification were achieved at 4.5 pM and 15 pM, respectively, using simple absorbance measurements, with effective operation demonstrated across various media. The sensor also obtains excellent selectivity when testing with other analytes, including glucose, amoxicillin, tetracycline, penicillin, ampicillin, and cephalexin. The capabilities of these ZnS: Mn/Chitosan-based sensors mark a significant advancement in antibiotic monitoring, offering promising applications in clinical settings for patient care and environmental surveillance, thereby playing a critical role in curbing the spread of antibiotic resistance globally.